PRODUKTIVITAS KINERJA GURU DAN MOTIVASI MENGAJAR - Jamiluddin Yacub (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2012)
Two factors determine the productivity of work so the teacher is the ability and willingness to teach, skills related to competence resulting from the level of education while teaching a willingness to do with motivation. Work productivity associated with the ratio between output and inputs used to produce outputs. An organization of educational institutions both government and private sector in issuing its products always require input in the form of raw materials, capital, energy, technology, human resources (HR), and so forth. But the most urgent input is itself a human resource for sophisticated and complete as any other input if human resources are not working then all the input there would be no meaning. The quality of human resources is determined from the level of education the longer time spent on education, the higher ability or competence in doing the work, so the higher the productivity of its work. In addition to educational level of labor productivity is also determined by the motivation is strong encouragement from the man to conduct their activities in order to achieve the goal, it is said that 90% of success is determined by the motivation of a person›s life while 10% is determined by intelligence.